Catullus and the Traditions of Ancient Poetry - Wheeler, Arthur Leslie (Toronto : University of California Press, 2021)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1934.
Intro -- FOREWORD -- PREFACE -- CONTENTS -- CHAPTER I. THE HISTORY OF THE POEMS -- CHAPTER II. KINDS AND TYPES OF POETRY -- CHAPTER III. THE BACKGROUND IN ROMAN POETRY -- CHAPTER IV. THE POET'S LIFE AND TRAINING -- CHAPTER V. THE POETIC TALE -- CHAPTER VI. THE ELEGIES -- CHAPTER VII. THE WEDDING POEMS -- CHAPTER VIII. THE SHORT POEMS -- LIST OF ABBREVIATIONS OF TITLES OF BOOKS, PERIODICALS, ETC. -- NOTES FOR CHAPTER I -- INDEX
Description based upon print version of record.
JSTOR
Keywords: Catullus, Gaius Valerius -- Knowledge and learning; Catullus, Gaius Valerius; Influence (Literary, artistic, etc.) -- History -- To 1500.; Latin poetry -- History and criticism; Greek poetry -- History and criticism; Poésie latine -- Histoire et critique; Poésie grecque -- Histoire et critique; Greek poetry; Influence (Literary, artistic, etc.); Latin poetry; Learning and scholarship; To 1500; Criticism, interpretation, etc; History